Effectiveness of Language Security Policy in Preserving the Omani National Identity - Al Ghusaini, Zahir Badar (Dirasat: Human and Social Sciences, 2024)
Objectives: This research aimed to identify the effectiveness of the linguistic security policy in preserving the Omani national identity in an effort to raise national awareness of the importance of protecting the Arabic language in everyday usage in the Sultanate of Oman. Methods: The research employed an inductive method, making observations on the pragmatic reality of the Arabic language in the Omani society and extrapolating this reality with the aim of developing applicable solutions that ensure Arabic is used correctly linguistically. Results: The findings confirm that it is necessary to formulate policies that ensure language security and give respect to the usage of Arabic language in the Sultanate of Oman in order to preserve the Omani identity which has language as one of its main pillars, and establishing an Omani Arabic Language Academy.Also, the governmental and private institutions in Oman must assume their responsibility to promote linguistic citizenship through proper linguistic circulation in their administrative reality, as well as the importance of having a specialized linguistic identity for official institutions that ensures the correct use of linguistic terms related to the institution’s tasks. Conclusion: The research clarified that the linguistic security policy will not be achieved without linguistic planning that preserves linguistic circulation in the Omani society, and the executive authorities bear responsibility for their procedural application.